2020
DOI: 10.5811/westjem.2020.8.47276
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Outpatient Care For Older Adults Discharged From The Emergency Department Reduces Recidivism

Abstract: Introduction: Older adults present unique challenges to both emergency clinicians and health systems. These challenges are especially evident with respect to discharge after an emergency department (ED) visit as older adults are at risk for short-term, negative outcomes including repeat ED visits. The aim of this study was to evaluate characteristics and risk factors associated with repeat ED utilization by older adults. Methods: ED visits among participants in the Reasons for Geographic and Racial Differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The second possibility is that our target population was too broad. Some researchers 12,18,29 contend that care transition interventions may only prove effective when targeted to those at highest risk of return or experiencing care fragmentation, such as those with advanced age, medical complexity, cognitive impairment, mental health issues, low health literacy, low social support 2,6,10,19,42,47,48 . Others argue that interventions targeting patients with modifiable risk factors would be more effective than using an undifferentiated approach 11,49,50 …”
Section: Discussionmentioning
confidence: 99%
“…The second possibility is that our target population was too broad. Some researchers 12,18,29 contend that care transition interventions may only prove effective when targeted to those at highest risk of return or experiencing care fragmentation, such as those with advanced age, medical complexity, cognitive impairment, mental health issues, low health literacy, low social support 2,6,10,19,42,47,48 . Others argue that interventions targeting patients with modifiable risk factors would be more effective than using an undifferentiated approach 11,49,50 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the GED guidelines and accreditation standards recommend identifying older adults at risk for adverse outcomes and address follow‐up care by connecting the patient with timely outpatient services 16–19 . A previous study reported that older adults who were discharged home after an ED visit and followed‐up with primary care and subspecialty care within 30 days had lower ED revisits 20 . However, it remains unclear how to accomplish an efficient referral order process and prompt outpatient care post ED visit.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lower medication adherence has been associated with a greater risk of stroke, 3,12 while being seen by a primary care provider after an emergency department visit has been shown to reduce recurrent emergency department visits. 13 Successful TOC is particularly challenging after stroke hospitalization. Physical disability, depression and cognitive impairment affect patients' ability to follow instructions, participate in educational activities, and navigate the complex healthcare system; socioeconomic and environmental factors may considerably affect access and utilization of posthospitalization stroke care that impact successful TOC and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower medication adherence has been associated with a greater risk of stroke, 3,12 while being seen by a primary care provider after an emergency department visit has been shown to reduce recurrent emergency department visits. 13…”
Section: Discussionmentioning
confidence: 99%